2014
DOI: 10.1002/chem.201402447
|View full text |Cite
|
Sign up to set email alerts
|

Protonation Switching to the Least‐Basic Heteroatom of Carbamate through Cationic Hydrogen Bonding Promotes the Formation of Isocyanate Cations

Abstract: We found that phenethylcarbamates that bear ortho-salicylate as an ether group (carbamoyl salicylates) dramatically accelerate OC bond dissociation in strong acid to facilitate generation of isocyanate cation (N-protonated isocyanates), which undergo subsequent intramolecular aromatic electrophilic cyclization to give dihydroisoquinolones. To generate isocyanate cations from carbamates in acidic media as electrophiles for aromatic substitution, protonation at the ether oxygen, the least basic heteroatom, is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 65 publications
(38 reference statements)
0
24
0
Order By: Relevance
“…To shed light on the origin of the difference in reactivity, we carried out DFT calculations to evaluate the activation energies of the individual steps in the reactions of the N ‐monomethyl and N , N ‐dimethyl carbamates. In our previous work, OC bond dissociation of the carbamate group was found to be accelerated in TfOH through the formation of intramolecular hydrogen bonding between the ether oxygen and ortho ‐salicylate carbonyl oxygen atoms ( SM‐2 , see Figure 4A) 16. 22…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…To shed light on the origin of the difference in reactivity, we carried out DFT calculations to evaluate the activation energies of the individual steps in the reactions of the N ‐monomethyl and N , N ‐dimethyl carbamates. In our previous work, OC bond dissociation of the carbamate group was found to be accelerated in TfOH through the formation of intramolecular hydrogen bonding between the ether oxygen and ortho ‐salicylate carbonyl oxygen atoms ( SM‐2 , see Figure 4A) 16. 22…”
Section: Resultsmentioning
confidence: 95%
“…We previously carried out a screening study of leaving groups and found that carbamates with ortho ‐salicylate as an ether group (carbamoyl salicylates) show dramatic acceleration of OC bond dissociation in strong acid, which leads to facile generation of the isocyanate cation ( N ‐protonated isocyanate; 1 c , Figure 1). 16 Herein, we describe the direct amidation of aromatic compounds with isocyanate cations generated from carbamoyl salicylates in trifluoromethanesulfonic acid (TfOH) at room temperature. We further characterized the chemoselectivity of these amidation reactions, including the compatibility with other electrophilic functionalities and the difference in reactivity for secondary and tertiary amide formation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25] Ryo Murashige and co-workers established intramolecular Friedel-Crafts cyclization of 1-(2-iso-cyanatoethyl)benzene derivatives (15) in the presence of trifluoromethane sulfonic acid. Trifluoromethane sulfonic acid serves as an efficient catalyst for the cyclization of 1-(2-iso-cyanatoethyl)benzene 15 rather the other tested Lewis/ Bronsted acid catalyst (Scheme 3).…”
Section: Intramolecular Cyclization Of Carbamate/ Urea/ Thiourea/ Isomentioning
confidence: 99%
“…The carbamate moiety plays a significant role in medicinal chemistry, not only because it is found in drugs but also for its attendance to many prodrugs [9]. In recent years, carbamate derivatives have motivated a large number of theoretical and experimental studies due to their application in drug design and discovery [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%